2013
DOI: 10.1108/ijsms-14-02-2013-b005
|View full text |Cite
|
Sign up to set email alerts
|

Value creation: assessing the relationships between quality, consumption value and behavioural intentions at sporting events

Abstract: Throughout this study, the authors sought to identify the antecedents and consequences of a multi-dimensional consumption-value construct. Data were collected from sports spectators in Japan (n=372) and the United States (n=396). The results indicate that three quality dimensions (functional, technical and aesthetic quality) have a significant impact on their respective value dimensions in the context of sporting events. Moreover, the constructs of entertainment and community prestige have positive effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 39 publications
3
36
0
7
Order By: Relevance
“…On the contrary, Yoshida, James, and Cronin (2013b) found that the major predictor of consumer behavioral intentions is positive affect in the college football setting. If the impact of posi tive affect varies across American and Japanese sports, the weak or nonsignificant effects of positive affect on behav ioral consequences might be implausible in American sport.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 89%
“…On the contrary, Yoshida, James, and Cronin (2013b) found that the major predictor of consumer behavioral intentions is positive affect in the college football setting. If the impact of posi tive affect varies across American and Japanese sports, the weak or nonsignificant effects of positive affect on behav ioral consequences might be implausible in American sport.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 89%
“…For example, this study did not include other attitudinal constructs also believed to influence consumer loyalty. For instance, researchers have found significant direct effects of relationship quality (Kim, Trail, & Ko, 2011), consumption value (Yoshida, James, & Cronin, 2013b), and brand image (Bauer, Stokburger-Sauer, & Exler, 2008) on consumer loyalty. In addition to the predictor variables we tested in this study, future research should examine the effects of additional variables on objective behavioral loyalty.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 98%
“…The consumption of sport through live game attendance is a leisure activity that can produce both hedonic and utilitarian value for game spectators (Yoshida, James, & Cronin, 2013). Live sporting events are inherently a hedonic and experiential product.…”
Section: Utilitarian and Hedonic Valuementioning
confidence: 99%